Factors Affecting User Satisfaction Mobile Banking - Rachmanto, Adi; Setiawan, Sony; Munggaran, Kharisma Puspa (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study was to determine the effect of system quality, perceived ease of use, and service quality on mobile banking user satisfaction. This research needs to be done because institutions and companies are currently required to have accounting information systems that provide satisfaction to their users. The use of information systems recently plays a role in supporting the interaction of companies and consumers, managing company activities, increasing individual productivity, assisting the decision-making process, and collaborating on the important roles of these companies to achieve competitive advantage. In order for mobile banking to provide satisfaction to its users, it needs to be supported by system quality, perceived ease of use, and service quality.The method used in this research is descriptive and verification method with a quantitative approach. The sample used in this research is 100 students who use mobile banking. The data analysis method used in this study is the Structural Equation Modeling (SEM) method using SmartPLS software. The results of this study indicate that system quality has a significant effect on user satisfaction with electronic-based accounting information systems, perceived ease of use has a significant effect on user satisfaction with electronic-based accounting information systems and service quality has a significant effect on user satisfaction with electronic-based accounting information systems for students who use mobile banking.